2004
DOI: 10.4049/jimmunol.172.5.2744
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Activity of Human Adult Microglia in Response to CC Chemokine Ligand 21

Abstract: The approximately 50 known chemokines are classified in distinct subfamilies: CXC, CC, CX3C, and C. Although the signaling of chemokines often is promiscuous, signaling events between members of these distinct chemokine classes are hardly observed. The only known exception so far is the murine CC chemokine ligand (CCL)21 (secondary lymphoid tissue chemokine, Exodus-2, 6Ckine), which binds and activates the murine CXC chemokine receptor CXCR3. However, this exception has not been found in humans. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 27 publications
1
45
0
Order By: Relevance
“…Furthermore, we were able to show that CCL21 activates microglia via the chemokine receptor CXCR3 (Biber et al, 2001(Biber et al, , 2002Rappert et al, 2002;Dijkstra et al, 2004). Subsequent studies showed that mice deficient for CXCR3 displayed no secondary activation of microglia in response to enthorinal cortex lesion.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Furthermore, we were able to show that CCL21 activates microglia via the chemokine receptor CXCR3 (Biber et al, 2001(Biber et al, , 2002Rappert et al, 2002;Dijkstra et al, 2004). Subsequent studies showed that mice deficient for CXCR3 displayed no secondary activation of microglia in response to enthorinal cortex lesion.…”
Section: Introductionmentioning
confidence: 83%
“…The expression plasmid for mCXCR3 (pcDNA3.1-mCXCR3) was described recently (Dijkstra et al, 2004), and the expression plasmid for mCCR7 (pRC/CMV-mCCR7) was a kind gift from Dr. U. Hoekpen and Dr. M. Lipp (Max-Delbrück-Centrumfür Molekulare Medizin, Berlin, Germany). Mock transfections were performed with empty pEGFP-N2 vector.…”
Section: Transfection Of Cells Ng108 and Hek293 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microglia activated by LPS stimulation in vitro (Dijkstra et al, 2006), in multiple sclerosis lesions (Serafini et al, 2006), and in models of experimental autoimmune encephalomyelitis during symptom onset and progression (Columba-Cabezas et al, 2003;Dijkstra et al, 2006), have been shown to upregulate the CCR7 receptor. Microglia also respond to CCL21 via lower-affinity activation of the CXCR3 receptor (Murphy et al, 2000;Biber et al, 2001;Rappert et al, 2002;Dijkstra et al, 2004). CXCR3 is also expressed by astrocytes and neurons; however, CCL21 is not a functional ligand for CXCR3 in these cells de Jong et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Also in some human cells, CCL21 is a functional ligand for endogenously expressed CXCR3 (Dijkstra et al, 2004;Poggi et al, 2004). To investigate whether CXCR3 can transduce the ligand signals in colon cancer cells, we first performed calcium mobilization assays.…”
Section: Expression Of Chemokine Receptors Cxcr3 Cxcr4 and Ccr7 In Cmentioning
confidence: 99%